A study of conceptual metaphors in music reviews in english and vietnamese - Phạm,Thị Ngọc Thảo (ĐHĐN., 2015)
This research investigated into the use of conceptual metaphors in English and Vietnamese music reviews. With the analysis of 365 instances of conceptual metaphorical expressions in both languages (171 items in English and 194 ones in Vietnamese), this thesis aimed to point out the semantic features as well as find out the similarities, the differences and the frequencies of occurrence of conceptual metaphors in music reviews in both languages. The qualitative and quantitative approach combining with descriptive and contrastive methods were exploited to help the researcher achieve the proposed aims and objectives. The findings presented 3 kinds of conceptual metaphors namely ontological metaphors, orientational metaphors and structural metaphors. In ontological metaphors, the four sub-types such as personification, object, substance and container metaphors were discussed and compared in linguistic and semantic features. In the same ways, orientational metaphors with its six sub-types including “success is up, failure is down”, “high pitch is up, low pitch is down”, “meaningful song is deep, meaningless song is shallow”, “good music is up”, “good voice is up”, “good emotion is up” were carefully discussed and presented. Interestingly, the description and comparison in detail in semantic and linguistic features of the ten minor types of structural metaphors under the ten source domains namely moving force, fire, architecture, verbal rhetoric, natural phenomenon, food, magic, kingdom, color and electric charge were the highlight of the thesis. Overall, this study is carried out with a hope to make a significant contribution in foreign language learning and teaching, translation practice and cross-culture communication. Specifically, this study is expected to facilitate the readers‟ comprehension in reading and studying music reviews.